2001
DOI: 10.1046/j.1469-1809.2001.6530285.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of four human Y‐specific microsatellites (DYS434, DYS437, DYS438, DYS439) for population and forensic studies

Abstract: In this work we present results on DYS434, DYS437, DYS438 and DYS439 loci studied in three population samples from North Portugal (N : 69), Macao (N : 59) and Mozambique (N : 64). Gene and haplotype diversity values are presented and compared. Gene diversity values ranged from 0.0290 to 0.0620 for DYS434 ; 0.0615 to 0.5959 for DYS437 ; 0.4906 to 0.6424 for DYS438 ; 0.5873 to 0.7038 for DYS439. The highest average gene diversity was found in Macao and the lowest in Mozambique. Haplotype diversity in Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
3

Year Published

2001
2001
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
2
3
0
3
Order By: Relevance
“…The additional marker causes a variation in haplotype diversity as follows: DYS437 (H = 0.9982 AE 0.0010, 143 haplotypes), DYS438 (H = 0.9986 AE 0.0009, 146 haplotypes) and DYS439 (H = 0.9994 AE 0.0008, 153 haplotypes). The level of discrimination obtained by additional typing of DYS439 confirms its usefulness for forensic purposes [12,24].…”
supporting
confidence: 59%
“…The additional marker causes a variation in haplotype diversity as follows: DYS437 (H = 0.9982 AE 0.0010, 143 haplotypes), DYS438 (H = 0.9986 AE 0.0009, 146 haplotypes) and DYS439 (H = 0.9994 AE 0.0008, 153 haplotypes). The level of discrimination obtained by additional typing of DYS439 confirms its usefulness for forensic purposes [12,24].…”
supporting
confidence: 59%
“…Gusmão et al 2002) whilst a unimodal distribution has been observed in Asia and Africa, and the locus is almost monomorphic in sub-Saharan populations . A similar pattern emerges for the pentanucleotide Y-STR DYS438 which has a bimodal allele frequency distribution in northern Portugal, but not in Mozambique (SE Africa) or in Asians from Macao (Gusmão et al 2001;Uchihi et al 2003).…”
Section: Introductionsupporting
confidence: 64%
“…The consensus repeat structure of the DYS437 locus has been reported to be (TCTA) m (TCTG) 2 (TCTA) 4 , and differences in the number of “m” reflect differences in alleles (Gusmao et al . 2001, 2002).…”
Section: Resultsmentioning
confidence: 99%